How to target apoptosis signaling pathways for the treatment of pediatric cancers - Fulda, Simone (Frontiers in Oncology, 2013)
Apoptosis represents one of the most important forms of cell death in higher organisms and is typically dysregulated in human cancers, including pediatric tumors. This implies that ineffective engagement of cell death programs can contribute to tumor formation as well as tumor progression. In addition, the majority of cytotoxic therapeutic principles rely on the activation of cell death signaling pathways in cancer cells. Blockade of signaling networks that lead to cell death can therefore confer treatment resistance. A variety of genetic and epigenetic events as well as dysfunctional regulation of signaling networks have been identified as underlying causes of cell death resistance in childhood malignancies. Apoptosis pathways can be therapeutically exploited by enhancing proapoptotic signals or by neutralizing antiapoptotic programs. The challenge in the coming years will be to successfully transfer this knowledge into the development of innovative treatment approaches for children with cancer.